Ultrasound‐assisted extraction of oil from hempseed (Cannabis sativa L.): Part 1. (18th July 2021) - Esposito, Marilena; Piazza, Laura
Abstract: BACKGROUND: Ultrasound‐assisted extraction of the intermediate product from the mechanical expression of hemp ( Cannabis sativa L.) seed oil was investigated to improve the overall expression yield without compromising oil quality. Complementary ultrasound technology was used as an out‐of‐line treatment carried out at 20 kHz frequency and optimized with respect to amplitude (80 and 152 μm), sonication time (2, 10, 20 min) and to the hemp paste properties, in particular its particle size and hydration, which drive the compressibility of the press cake. RESULTS: Under the conditions evaluated, the optimal ultrasound treatment was found to be the one applied on the hydrated press cake for 2 min at 152 μm, which resulted in an oil yield of 13.4%, with an increase in extraction efficiency equal to 73% with respect to the control (untreated press cake). Sonication had a positive effect on the press cake texture and on the extracted oil antioxidant activity. Soaked samples treated for 2 min at 152 μm yielded the lowest hardness. Oil recovered from soaked samples treated at 80 μm and 152 μm ultrasound for 2 min had the highest antioxidant capacity. CONCLUSIONS: The technological results gathered in the present investigation are preliminary to the design and engineering of scaled‐up equipment that combines the mechanical screw expression and the in‐line ultrasound unit. © 2021 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.